Guidelines for project evaluation - United Nations Industrial Development Organization; Marglin, Stephen A.; Sen, Amartya (New York : United Nations, 1972)
This publication represents the cumulative experience of UNIDO in the methodology and practice of national benefit-cost analysis for industrial project preparation and evaluation.
At head of title: United Nations Industrial Development Organization, Vienna.
"United Nations publication. Sales no.: E.72.II.B.11."
Includes bibliographical references.
osa 05/05/2017
Loans
Keywords: Government spending policy; Expenditures, Public